2015
DOI: 10.3233/bme-151353
|View full text |Cite
|
Sign up to set email alerts
|

Study of cervical muscle response and injury of driver during a frontal vehicle collision

Abstract: Abstract. Frontal vehicle collisions can cause injury to a driver's cervical muscles resulting from intense changes in muscle strain and muscle load. This study investigated the influence of collision forces in a sled test environment using a modified Hybrid III 50 th percentile dummy equipped with simulated spring-type muscles. Cervical muscle responses including strain and load of the sternocleidomastoid (SCM), splenius capitis (SPL), and trapezius (TRP) were analyzed, and muscle injury was assessed. The SCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It is reasonable to assume that the moment arm variations do not change significantly the load distribution among the neck extensors, but the cumulative neck extensor force increases as the moment arm shortens. Gao et al [57] observed the same level of the peak load and timing for trapezius and semispinalis muscles, suggesting that measuring the stress of the trapezius muscle can also indicate the dynamic response for other neck extensors. With measuring the muscle tension on upper trapezius, muscle wrapping is already taken into account, providing a more favourable input parameter for estimating neck loads during frontal impacts.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that the moment arm variations do not change significantly the load distribution among the neck extensors, but the cumulative neck extensor force increases as the moment arm shortens. Gao et al [57] observed the same level of the peak load and timing for trapezius and semispinalis muscles, suggesting that measuring the stress of the trapezius muscle can also indicate the dynamic response for other neck extensors. With measuring the muscle tension on upper trapezius, muscle wrapping is already taken into account, providing a more favourable input parameter for estimating neck loads during frontal impacts.…”
Section: Discussionmentioning
confidence: 99%